2021
DOI: 10.3390/ijms22094390
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycolysis Suppresses Cell Proliferation and Tumor Progression In Vivo: Perspectives for Chronotherapy

Abstract: A high rate of glycolysis is considered a hallmark of tumor progression and is caused by overexpression of the enzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3). Therefore, we analyzed the possibility of inhibiting tumor and endothelial cell metabolism through the inhibition of PFKFB3 by a small molecule, (E)-1-(pyridin-4-yl)-3-(quinolin-2-yl)prop-2-en-1-one (PFK15), as a promising therapy. The effects of PFK15 on cell proliferation and apoptosis were analyzed on human umbilical vein endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our recent study confirms that the possibility to target metabolic pathways at a specific time may be a promising approach. We found that administration of glycolysis inhibitor 1-(4-pyridinyl)-3-(2-quinolinyl)-2-propen-1-one (PFK15) at different times can result in a significant reduction in the tumour progression [60]. Another study on nude mice with implanted breast tumour cells into the femoral artery proved an increased arterial glucose uptake by tumour cells and lactate concentration in the blood.…”
Section: Circadian Regulation Of Glucose Metabolismmentioning
confidence: 97%
“…Our recent study confirms that the possibility to target metabolic pathways at a specific time may be a promising approach. We found that administration of glycolysis inhibitor 1-(4-pyridinyl)-3-(2-quinolinyl)-2-propen-1-one (PFK15) at different times can result in a significant reduction in the tumour progression [60]. Another study on nude mice with implanted breast tumour cells into the femoral artery proved an increased arterial glucose uptake by tumour cells and lactate concentration in the blood.…”
Section: Circadian Regulation Of Glucose Metabolismmentioning
confidence: 97%
“…Often referred to as the gatekeeper of glycolysis [ 101 ], PFK is highly expressed in many tumor types, exerting regulatory control over cancer cell growth and metabolism [ 102 , 103 , 104 ]. In recent years, the development of new PFK inhibitors, including 3PO [ 69 ], PFK15 [ 70 ], and PFK158 [ 71 ], has shown promising results in pre-clinical models…”
Section: Therapeutic Strategies Targeting the Warburg Effectmentioning
confidence: 99%
“…In recent years, various small molecule inhibitors targeting glycolysis enzymes have emerged, showing promising results in both pre-clinical [ 69 , 70 , 71 , 77 ] and clinical trials [ 76 ], highlighting the therapeutic interest of the Warburg effect. The acidification of the extracellular medium and relative basification of the cellular cytoplasm induces chemoresistance by neutralizing weakly basic drugs such as paclitaxel, making it difficult for them to cross the membrane [ 31 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Among the list of candidate drugs that target PFKFB3, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO), 1-(4-pyridinyl)-3-(2-quinolinyl)-2-propen-1-one (PFK15), and 1-pyridin-4-yl-3-[7-(trifluoromethyl)-quinolin-2-yl]-prop-2-en-1-one (PFK158) have drawn more attention than others[ 181 ]. It was found that 3PO and PFK15 inhibit cell proliferation, reduce tumor growth, attenuate angiogenesis, prevent fibrogenesis, and increase cell death in pre-clinical studies using GI cancer cell lines, transgenic mice, xenograft mouse models, and HCC rat models[ 182 - 189 ]. Intriguingly, it was also found that 3PO suppresses glucose uptake via a 14C-2-DG tracing system[ 184 ].…”
Section: Unlocking the Potential Of Glucose Metabolism Targets In Gi ...mentioning
confidence: 99%